Development of the theoretical construction model of muslim religious character with confirmatory factor analysis to develop a measurement scale - Mami Hajaroh,; Dwiningrum, Siti Irene Astuti; Rukiyati, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Religious character is a positively measured moral value based on a permanent educational process, to help create an ethical framework and act as a socialization agent. This helps in building positive values such as love, empathy, respect, and harmony. Therefore, this study aims to determine a theoretical religious character construction model, for the development of a measurement scale. A quantitative approach was used by empirically testing the hypothetical factors of this theoretical character. A total of 320 respondents were also utilized as the population, with data measurement using the Aiken's-V formula, Confirmatory Factor Analysis (CFA), and Structural Equation Modelling (SEM). The results showed that (1) The theoretical construction model for religious character was determined by 6 indicators, namely intellect, belief, commitment, ritual, experience, and consequence, which were subsequently identified as moral knowledge, feelings, and actions, (2) The theoretical construction of this variable was declared fit due to meeting the eligibility criteria for the goodness-of-fit model on the AFI (absolute fit indices), IFI (incremental fit indices), PFI (parsimony fit indices), and critical-N. This construction had a reliability of 0.95, confirming that the model was fit for utilization, based on the compilation of a scale to measure students' religious character. These analytical results also helped in developing a religious character learning model.